Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine over which interval the function [tex]\( g(t) = -(t-1)^2 + 5 \)[/tex] has an average rate of change of zero, we need to follow these steps:
1. Recall the formula for the average rate of change of a function:
The average rate of change of [tex]\( g(t) \)[/tex] over the interval [tex]\([a, b]\)[/tex] is given by:
[tex]\[ \text{Average Rate of Change} = \frac{g(b) - g(a)}{b - a} \][/tex]
2. Evaluate [tex]\( g(t) \)[/tex] at the interval endpoints for each interval:
Let's look at the intervals one by one and compute [tex]\( g(a) \)[/tex] and [tex]\( g(b) \)[/tex] for [tex]\( a \)[/tex] and [tex]\( b \)[/tex] being the endpoints of the intervals.
### (A) Interval [tex]\([-2, 0]\)[/tex]
- [tex]\( a = -2 \)[/tex]
- [tex]\( b = 0 \)[/tex]
[tex]\[ g(-2) = -((-2) - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ g(0) = -(0 - 1)^2 + 5 = -1 + 5 = 4 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(0) - g(-2)}{0 - (-2)} = \frac{4 - (-4)}{2} = \frac{4 + 4}{2} = 4 \][/tex]
### (B) Interval [tex]\([-4, -3]\)[/tex]
- [tex]\( a = -4 \)[/tex]
- [tex]\( b = -3 \)[/tex]
[tex]\[ g(-4) = -((-4) - 1)^2 + 5 = -25 + 5 = -20 \][/tex]
[tex]\[ g(-3) = -((-3) - 1)^2 + 5 = -16 + 5 = -11 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(-3) - g(-4)}{-3 - (-4)} = \frac{-11 - (-20)}{1} = \frac{-11 + 20}{1} = 9 \][/tex]
### (C) Interval [tex]\([-2, 4]\)[/tex]
- [tex]\( a = -2 \)[/tex]
- [tex]\( b = 4 \)[/tex]
[tex]\[ g(-2) = -((-2) - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ g(4) = -(4 - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(4) - g(-2)}{4 - (-2)} = \frac{-4 - (-4)}{6} = \frac{-4 + 4}{6} = 0 \][/tex]
### (D) Interval [tex]\([1, 4]\)[/tex]
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 4 \)[/tex]
[tex]\[ g(1) = -(1 - 1)^2 + 5 = 5 \][/tex]
[tex]\[ g(4) = -(4 - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(4) - g(1)}{4 - 1} = \frac{-4 - 5}{3} = \frac{-9}{3} = -3 \][/tex]
3. Analyze the results:
Among the computed average rates of change, we see that the average rate of change is zero for interval [tex]\([-2, 4]\)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{-2 \leq t \leq 4} \][/tex]
1. Recall the formula for the average rate of change of a function:
The average rate of change of [tex]\( g(t) \)[/tex] over the interval [tex]\([a, b]\)[/tex] is given by:
[tex]\[ \text{Average Rate of Change} = \frac{g(b) - g(a)}{b - a} \][/tex]
2. Evaluate [tex]\( g(t) \)[/tex] at the interval endpoints for each interval:
Let's look at the intervals one by one and compute [tex]\( g(a) \)[/tex] and [tex]\( g(b) \)[/tex] for [tex]\( a \)[/tex] and [tex]\( b \)[/tex] being the endpoints of the intervals.
### (A) Interval [tex]\([-2, 0]\)[/tex]
- [tex]\( a = -2 \)[/tex]
- [tex]\( b = 0 \)[/tex]
[tex]\[ g(-2) = -((-2) - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ g(0) = -(0 - 1)^2 + 5 = -1 + 5 = 4 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(0) - g(-2)}{0 - (-2)} = \frac{4 - (-4)}{2} = \frac{4 + 4}{2} = 4 \][/tex]
### (B) Interval [tex]\([-4, -3]\)[/tex]
- [tex]\( a = -4 \)[/tex]
- [tex]\( b = -3 \)[/tex]
[tex]\[ g(-4) = -((-4) - 1)^2 + 5 = -25 + 5 = -20 \][/tex]
[tex]\[ g(-3) = -((-3) - 1)^2 + 5 = -16 + 5 = -11 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(-3) - g(-4)}{-3 - (-4)} = \frac{-11 - (-20)}{1} = \frac{-11 + 20}{1} = 9 \][/tex]
### (C) Interval [tex]\([-2, 4]\)[/tex]
- [tex]\( a = -2 \)[/tex]
- [tex]\( b = 4 \)[/tex]
[tex]\[ g(-2) = -((-2) - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ g(4) = -(4 - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(4) - g(-2)}{4 - (-2)} = \frac{-4 - (-4)}{6} = \frac{-4 + 4}{6} = 0 \][/tex]
### (D) Interval [tex]\([1, 4]\)[/tex]
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 4 \)[/tex]
[tex]\[ g(1) = -(1 - 1)^2 + 5 = 5 \][/tex]
[tex]\[ g(4) = -(4 - 1)^2 + 5 = -9 + 5 = -4 \][/tex]
[tex]\[ \text{Average Rate of Change} = \frac{g(4) - g(1)}{4 - 1} = \frac{-4 - 5}{3} = \frac{-9}{3} = -3 \][/tex]
3. Analyze the results:
Among the computed average rates of change, we see that the average rate of change is zero for interval [tex]\([-2, 4]\)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{-2 \leq t \leq 4} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.